EARLY DETECTION OF NON-COMMUNICABLE DISEASES THROUGH BLOOD PRESSURE AND BLOOD SUGAR SCREENING DURING HEALTH CHECK ACTIVITIES IN THE 26 ILIR REGION - Rumentalia Sulistini; Syokumawena Syokumawena; Devi Mediarti; Jawiah Jawiah (Universitas Muhammadiyah Sumatera Barat, 2026)
Non-Communicable Diseases (NCDs) remain the most prevalent disease in Indonesia. Early screening to detect NCDs is necessary in the hope that people will not experience further complications and improve their quality of life. The goal of this community service is to achieve the number of people undergoing screening and to increase public knowledge. This early detection activity was carried out in the 26 Ilir area with stages of preparation, implementation, and evaluation. There were 65 participants aged 18-84 years. The results of this activity were data on blood pressure and blood glucose examinations, and education about problems experienced by participants, especially those with hypertension and diabetes. This activity is planned to become a program for the area around the campus and expand the activity area.